1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Function is F(n) = n(n+1)

  1. Oct 15, 2008 #1
    F(n) = 2+4+6=...+2n
    I know the expression that represents the given function is F(n) = n(n+1),

    my question is F(n) = 3+5+7...2n the same F(n) = n(n+1)< if not can anyone expain?

  2. jcsd
  3. Oct 15, 2008 #2


    User Avatar
    Science Advisor

    Re: Recursion

    Please correct! You have a sequence of odd numbers, but the end term is even!
  4. Oct 16, 2008 #3
    Re: Recursion

    This was gone into from General Math: Simple Sequences. The nth term is

    [tex] \sum_1^n (2j-1)=n^2. [/tex] Or: 1=1, 1+3=2^2, 1+3+5 = 3^2, etc...
    Last edited: Oct 16, 2008
  5. Oct 16, 2008 #4


    User Avatar
    Science Advisor

    Re: Recursion

    Why should they have the same sum when you are summing different numbers?

    It is not to difficult to show that if you have any arithmetic sequence: an= a+ id, where a and d are fixed and i ranges from 1 to n, sums to n times the average of a1 and an: n*(a+ d+ (a+ nd))/2= n(a+ (d/2)(n+1)).

    In the case of 2+ 4+ 6+ ...+ 2n, a= 0 and d= 2. The sum is n(0+ (2/2)(n+1)= n(n+1)
    In the case of 1+ 3+ 5+ ...+ 2n+1, a= -1 and d= 2. The sum is n(-1+ (2/2)(n+1))= n2.
  6. Oct 16, 2008 #5
    Re: Recursion

    Thank you all for your help in explaining this, I appreciate it greatly.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook